Beyond the modern age: an archaeology of contemporary culture - Goudzwaard, B. (IVP Academic, an imprint of InterVarsity Press, 2017)
The modern age has produced global crises that modernity itself seems incapable of resolving--deregulated capitalism, consumerism, economic inequality, militarization, overworked laborers, environmental destruction, insufficient health care, and many other problems. The future of our world depends on moving beyond the modern age. Bob Goudzwaard and Craig G. Bartholomew have spent decades listening to their students and reflecting on modern thought and society. In Beyond the Modern Age they explore the complexities and challenges of our time. Modernity is not one thing but many, encompassing multiple worldviews that contain both the source of our problems and the potential resources for transcending our present situation. Through an archaeological investigation and critique of four modern worldviews, Goudzwaard and Bartholomew demonstrate the need for new ways of thinking and living that overcome the relentless drive of progress. They find guidance in the work of René Girard on desire, Abraham Kuyper on pluralism and poverty, and Philip Rieff on culture and religion. These and other thinkers point the way toward a solution to the crises that confront the world today. Beyond the Modern Age is a work of grand vision and profound insight. Goudzwaard and Bartholomew do not settle for simplistic analysis and easy answers but press for nuanced engagement with the ideologies and worldviews that shape the modern age. The problems we face today require an honest, interdisciplinary, and global dialogue. Beyond the Modern Age invites us to the table and points the way forward. --